Intercultural Competences in Health Care - Jehovah's Witnesses - Elżbieta Bernaciak; Paulina Farbicka; Aleksandra Jaworska-Czerwińska; Renata Szotkiewicz (Journal of Education, Health and Sport, 2019)
After Poland's accession to the European Union, borders were opened and migrations from many culturally different countries intensified, which led to an increase in immigrants and refugees assimilating in Poland. Numerous ethnic, religious, linguistic and cultural groups existed and exist in Poland. All of these groups benefit from health services. The above situation requires medical personnel to perceive the patient through the prism of his biological, psychological, social and health problems, as well as in terms of spiritual needs of religions, as well as beliefs and socio-cultural origin. Therefore, knowledge about the cultural differences of healthcare service recipients and shaping intercultural sensitivity among healthcare workers is essential. This work examines multiculturalism in health care based on the example of the confession of Jehovah's Witnesses. Its aim was to get to know the health service opinions regarding cultural competences in specific work with patients.